Habilidades Sociais e Dependência Nicotínica em Universitários Fumantes - Rondina, Regina de Cássia [UNESP]; Martins, Raul [UNESP]; Manzato, Antonio José [UNESP]; Terra, Ana Paula [UNESP] (Sociedade Portuguesa de Psicologia da Saúde, 2013)
The aim of this study was investigate the relationship between social skills and nicotine dependence. 97 undergraduate smokers from a public university filled out a questionnaire, the Fagerstrom Test for Nicotine Dependence and the Social Skills Inventory (Del Prette & Del Prette, 2001). Among the subjects, 20.61% were considered nicotine dependent. The Analysis of Variance detected higher scores, on average, for Factor F1 (Confrontation with risk) among addicted smokers on SSI. Applying Multivariate Analysis of Variance, only the knowledge area remains associated with the scores of SSI. There might be association between dependence and the F1 factor of the SSI, among students from the health area. New studies are necessary to verify those associations.

O objetivo deste trabalho foi investigar a relação entre habilidades sociais e dependência nicotínica. Participaram do estudo 97 acadêmicos fumantes de uma universidade pública que preencheram um questionário, o Teste de Fagerstrom para Dependência Nicotínica e o Inventário de Habilidades Sociais (Del Prette &Del Prette, 2001). Dentre os participantes, 20,61% foram considerados dependentes à nicotina. A Análise de Variância detectou que fumantes dependentes obtiveram, em média, maiores escores no Fator F1 (Enfrentamento com Risco) do IHS. Via Análise de Variância Multivariada, apenas a área do conhecimento permanece associada aos escores do IHS. Discute-se a possibilidade de associação entre dependência e o Fator F1 do IHS, em acadêmicos da área de saúde. Novos estudos são necessários, para averiguar essas associações.
Social Skills and Nicotine Dependence in Undergraduate Smokers
Keywords: tabagismo; dependência; nicotina; habilidades sociais; smoking behavior; addiction; nicotine; social skills